Pengaruh Literasi Keuangan dan Self Control terhadap Perilaku dan Sikap Keuangan Mahasiswa Pendidikan Ekonomi UNS - Qory Afdhila; Jonet Ariyanto Nugroho (Journal on Education, 2023)
This study investigates the impact of financial literacy and self-control on the financial behaviours and attitudes of Economics Education Students at Sebelas Maret University Class of 2019-2022. Employing a simple random sampling method, data were gathered from 207 respondents. A descriptive quantitative research approach was adopted, with descriptive statistical methods and logistic regression analysis were used for data analysis. The findings reveal that financial literacy has a positive and significant influence on both the financial behaviour at a 1% significance level, and the financial attitudes of Sebelas Maret University Economics Education students at a 1% significance level. In contrast, self-control does not significantly influence either the financial behaviour or attitudes of these students dan and both lacking statistical significance.